Impact of ABO blood group on bleeding complications after surgery for acute type A aortic dissection. Issue 4 (June 2021) - Guné, Henrik; Larsson, Mårten; Nozohoor, Shahab; Herou, Erik; Luts, Cecilia; Ragnarsson, Sigurdur; Samuelsson, Maria; Sjögren, Johan; Svensson, Peter J.; Zindovic, Igor
Abstract : N/A: Excessive bleeding is a serious complication associated with impaired survival after surgery for acute type A aortic dissection (ATAAD). Different ABO blood groups are associated with variable levels of circulating von Willebrand factor and therefore potentially altered risks of surgical haemorrhage. The current study aimed to assess the impact of blood group on bleeding complications after ATAAD surgery. This was a retrospective cohort study including 336 patients surgically treated for ATAAD between January 2004 and January 2019. Patients with blood group O were compared with non-O patients. In total, 152 blood group O patients were compared with 184 non-O patients. There were no differences in rates of massive bleeding (27.0 vs. 25.5%, P = 0.767) or re-exploration for bleeding (16.4 vs. 13.0%, P = 0.379) in blood group O and non-O patients, respectively. Median chest tube output 12 h after surgery was 520 ml (350–815 ml) in blood group O and 490 ml (278–703 ml) in non-O patients ( P = 0.229). Blood group O patients received more fibrinogen concentrate (6.1 ± 4.0 vs. 4.9 ± 3.3 g, P = 0.023) but administered units of packed red blood cells [5 (2–8) vs. 4 (2–9) U, P = 0.736], platelets [4 (2–4) vs. 3 (2–5) U, P = 0.521] or plasma [4 (1–7) vs. 4 (0–7) U, P = 0.562] were similar. This study could not demonstrate any association between blood group and bleeding after surgery for ATAAD. It cannot be ruled out that potential differences were levelled out by blood group O patients receiving significantly more fibrinogen concentrate.